FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN - Tanuwijaya, Suwandhi; Cahyadi, Hadi (Jurnal Paradigma Akuntansi, 2024)
The purpose of the study was to obtain empirical evidence regarding the effect of leverage, firm size, managerial stock ownership, audit committee, and asset structure on firm performance. The study used 117 data samples from manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2020 period. The research uses Microsoft Office 365 and Eviews 12 software in terms of data processing. The results obtained from the study are that leverage has a negative effect on company performance, firm size has a negative effect on company performance, managerial share ownership has a negative effect on company performance, audit committees have a positive effect on company performance, and asset structure has a negative effect on company performance.